The Universe in the Paradigm of Tawhid (A Study of Murtada Mutahhari's Thoughts) - Ihwan Amalih; Fitriyani (Penerbit Hellow Pustaka, 2025)
Allah gave a mandate to humans to become Caliphs. However, humans experience a crisis of spiritual values and a paradigm error in looking at nature. As a result, nature is experiencing an environmental crisis. So nature needs an alternative paradigm so that natural problems can be resolved. One of them is the tawhid paradigm which is considered capable of solving problems in nature. Murtada Mutahhari is a contemporary philosopher with the uniqueness of the principle of tawhid of the universe in looking at humans. The problems raised in this study are how the universe in the paradigm of tawhid and the relationship between humans and nature in the paradigm of tawhid from the perspective of Murtada Mutahhari . This research tries to reveal how the universe in the paradigm of tawhid on Murtada Mutahhari 's thought. This research uses a qualitative approach (library research) by using descriptive data analysis. This research results in the finding that (1) The conception of tawhid is a conception that has all the characteristics where the conception of tawhid is an awareness of the facts about the existence of the universe thanks to the wise will of the creator. The conception of tawhid regarding the universe provides enthusiasm and purpose for life. Where humans in the conception of tawhid are placed for a holy purpose and a high degree of other creatures. (2) According to Murtada Mutahhari , the Tawhid Paradigm is a new paradigm that can solve problems in nature. Because in the paradigm of tawhid, humans are the essence and important elements of a life that is a core of nature. Humans are not just homo erectus (two-legged animals) who can speak. But humans are the most superior creatures to other creatures such as angels, heaven, and earth. That is why humans are made khalifah (representatives) of Allah on earth.